Experimental investigation on the strength and stiffness of 3D printed stainless steel S/S-316L parts - Muhammad Syahimi Bin Salim (Nanyang Technological University, 2023)
Additive manufacturing (AM) is a method of producing an object layer by layer. It is the reverse of the machining process which involves removing small amounts of a solid material block at a time until it is the finished product. Additive manufacturing metal such as stainless steel has been an ongoing trend for the past years, but there are limitations to additive manufacturing such as the fatigue strength. This study aims to evaluate the strength and stiffness of 3D printed metal by comparing the properties between 3D printed and conventional manufactured stainless steel using various mechanical testing to provide as an alternative material in the engineering industry.